Poliovirus serological assay after the cVDPV1 outbreak in Papua New Guinea: a cross-sectional study from 2020 to 2021Research in context - William Pomat; Rocio Lopez Cavestany; Visalakshi Jeyaseelan; Rebecca Ford; Janet Gare; Tigran Avagyan; Varja Grabovac; Deborah Bettels; Dessie Mekonnen; Kathryn Ann Vetter Jones; Bernardo Alfredo Mainou; Ondrej Mach (Elsevier, 2024)
Summary: Background: In June 2018, a type 1 circulating vaccine-derived poliovirus (cVDPV1) outbreak was declared in Papua New Guinea (PNG), resulting in a total of 26 paralytic confirmed cases. Eight vaccination campaign rounds with bivalent oral poliovirus vaccine (bOPV) were carried out in response. Prevalence of neutralizing polio antibodies in children was assessed two years after the outbreak response was completed. Methods: We conducted a cross-sectional serological survey among children aged 6 months-10 years selected from six provinces in PNG to evaluate seroprevalence of neutralizing polio antibodies to the three poliovirus serotypes and analyse sociodemographic risk factors. Findings: We included 984 of 1006 enrolled children in the final analysis. The seroprevalence of neutralizing polio antibodies for serotype 1, 2 and 3 was 98.3% (95% CI: 97.4-98.9), 63.1% (95% CI: 60.1-66.1) and 95.0% (95% CI: 93.6-96.3), respectively. Children <1 year had significantly lower type 1 seroprevalence compared to older children (p < 0.001); there were no significant differences in seroprevalence among provinces. Interpretation: PNG successfully interrupted transmission of cVDPV1 with several high coverage bOPV campaigns and seroprevalence remained high after two years. The emergence of cVDPV strains underscores the importance of maintaining high levels of routine immunization coverage and effective surveillance systems for early detection. Funding: World Health Organization through a Rotary International IPPC grant.